Selective focus in reading: a social-based explanation - Lux, Paul; Grabe, William (Lenguas Modernas, 2017)
The purpose of this article is to describe applications of multivariate quantiatative research approaches to contrastive rhetoric research. We will first introduce the notion of contrastive rhetoric and evidence supporting the notion. We will then present the rationale for the multivariate approach used here. Two separate studies using a multivariate approach will then be described. One examines patterns of variation in English and Brazilian Portuguese newspaper editorials (Dantas-Whitney and Grabe to appear); the second examines variations in writing among Ecuadorian Spanish and Anglo-American English university students (Lux 191). Results of these studies suggest that a multivariate approach to text analysis, and specifically to contrastive rhetoric, is a productive line of research.